2021
DOI: 10.1093/genetics/iyab086
|View full text |Cite
|
Sign up to set email alerts
|

Neuronal postdevelopmentally acting SAX-7S/L1CAM can function as cleaved fragments to maintain neuronal architecture inCaenorhabditis elegans

Abstract: Whereas remarkable advances have uncovered mechanisms that drive nervous system assembly, the processes responsible for the lifelong maintenance of nervous system architecture remain poorly understood. Subsequent to its establishment during embryogenesis, neuronal architecture is maintained throughout life in the face of the animal’s growth, maturation processes, the addition of new neurons, body movements, and aging. The C. elegans protein SAX-7, homologous to the vertebrate L1 protein family of neural adhesi… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 110 publications
0
7
0
Order By: Relevance
“…Interestingly, SAX-7 was recently shown to undergo proteolytic cleavage in vivo and to function, at least in some contexts, in its cleaved form (Desse et al, 2021). All of our mutant alleles are predicted to produce truncated SAX-7 proteins reminiscent of the cleaved SAX-7 products (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Interestingly, SAX-7 was recently shown to undergo proteolytic cleavage in vivo and to function, at least in some contexts, in its cleaved form (Desse et al, 2021). All of our mutant alleles are predicted to produce truncated SAX-7 proteins reminiscent of the cleaved SAX-7 products (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…We therefore examined a molecular null allele of sax-7 generated by CRISPR/Cas9-mediated deletion of the entire sax-7 locus (sax-7(qv30), Fig. 1D) (Desse et al, 2021).…”
Section: The Sax-7 Cytoplasmic Tail Is Required For Urx and Bag Dendr...mentioning
confidence: 99%
“…We wanted to find out whether offspring of heat-shocked mothers expressed higher basal levels of the molecular chaperone proteins HSP70 (HSP-1 in C. elegans) and HSP90 (DAF-21 in C. elegans), which inhibit HSF-1 activation but can increase thermotolerance, because this might explain the apparently contradictory results of increased stress resilience and decreased HSF-1 stress inducibility. However, this was also not the case; western blot analysis using antibodies to endogenous hemagglutinin (HA)-tagged HSP-1 (Figure S3E) and DAF-21 (Figure S3F; see also Blanchette et al, 2015;Desse et al, 2021) showed no differences in these protein levels between offspring of stressed mothers and non-stressed mothers. Inducible HSP-70 protein levels were also not higher in animals that had experienced early-life stress exposure (Figure S3G).…”
Section: Introductionmentioning
confidence: 94%
“…Briefly, the morphology of every neuron and glial cell is highly stereotyped and has been carefully catalogued; individual cells can be readily visualized in live intact animals throughout life; and it is straightforward to perform forward genetic screens by visually identifying mutants that show aberrant morphology of single neurons or glial cells. Recent screens have revealed roles for extracellular factors (i.e., ECM components and cell surface adhesion molecules) in diverse aspects of neurodevelopment, including neuroblast migration [2][3][4], axon and dendrite extension [5][6][7][8][9], fasciculation of neurites into nerve bundles [10][11][12][13][14][15], and synapse development [16][17][18][19][20][21].…”
Section: Introductionmentioning
confidence: 99%